Early-drug development in the era of immuno-oncology: are we ready to face the challenges?. (26th June 2018) - Ochoa de Olza, M; Oliva, M; Hierro, C; Matos, I; Martin-Liberal, J; Garralda, E
Abstract: The classical development of drugs has progressively faded away, and we are currently in an era of seamless drug-development, where first-in-human trials include unusually big expansion cohorts in the search for early signs of activity and rapid regulatory approval. The fierce competition between different pharmaceutical companies and the hype for immune combinations obliges us to question the current way in which we are evaluating these drugs. In this review, we discuss critical issues and caveats in immunotherapy development. A particular emphasis is put on the limitations of pre-clinical toxicology studies, where both murine models and cynomolgus monkeys have underpredicted toxicity in humans. Moreover, relevant issues surrounding dose determination during phase I trials, such as dose–escalation methods or flat versus body-weight dosing, are discussed. A proposal of how to face these different challenges is offered, in order to achieve maximum efficacy with minimum toxicity for our patients.